(untitled) - Frimodt, Claus (Oxford, 1995)
Each two-page spread in the new Multilingual Illustrated guide to the world's commercial coldwater fish is a succinct and highly-visual presentation of all that is pertinent to a particular species - over 170 species are covered in all. Information is presented, wherever possible, in tabular and diagramatic format for ease and speed of use - textual description is kept to a minimum. The guide encapsulates a wealth of information vital to all who are concerned with coldwater fish of commercial importance, including traders, processors, fisheries scientists, commercial fishermen, and fisheries economists.
Keywords: Fisheries,Fishes,Warmwater fishes; Polyglot,Polyglot